The Effect of Timeliness, Work Quality, Effectiveness, and Independence on Employee Performance - Barus, Imelda; Muhani, Muhani; Hasrun, Andi; Yusuf, Ramdan; Susilowati, Teti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Employee performance plays a crucial role in determining organizational productivity and sustainability. This study aims to examine the influence of punctuality, work quality, effectiveness, and independence on employee performance at PT HIT in Kudus using a quantitative approach. Punctuality reflects an employee's ability to complete tasks according to a predetermined schedule, work quality emphasizes accuracy and conformity to standards, effectiveness refers to the optimal utilization of resources to achieve goals, and independence describes an employee's ability to perform tasks independently. This study used a survey method involving 100 PT HIT employees in Kudus selected using a census sampling technique. Data were collected through a structured questionnaire measured using a 5-point Likert scale. Data were analyzed using SPSS version 26 through validity and reliability tests, normality tests, multiple linear regression analysis, t-tests, and F-tests. The results indicate that punctuality, work quality, effectiveness, and independence each have a positive and significant influence on employee performance at PT HIT in Kudus, both partially and simultaneously. The coefficient of determination (R²) indicates that 65% of the variation in employee performance at PT HIT in Kudus can be explained by these variables. These findings highlight the importance of time management, quality orientation, effective work processes, and employee autonomy in improving organizational performance.